2020
DOI: 10.1111/cobi.13591
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of stakeholders’ environmental threat perceptions following mass coral bleaching of the Great Barrier Reef

Abstract: Managing human use of ecosystems in an era of rapid environmental change requires an understanding of diverse stakeholders' behaviors and perceptions to enable effective prioritization of actions to mitigate multiple threats. Specifically, research examining how threat perceptions are shared or diverge among stakeholder groups and how these can evolve through time is increasingly important. We investigated environmental threat perceptions related to Australia's Great Barrier Reef and explored their association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 54 publications
(94 reference statements)
1
7
0
Order By: Relevance
“…strengthen the continuous training between the different professions of the sea 45,52,55 Encourage stakeholder consultation (consultation) consult with stakeholders to determine the socioeconomic effects of strong protection, for the establishment of strategies, objectives, and regulations 45,55,65 Further communicate about the role of MPAs (communication) develop a clear, long-term communication strategy to promote the results of the researchers' work and raise awareness of the benefits of MPAs 45,49,[65][66][67] Increase and sustain the MPA budget (budget) increase and sustain the MPA budget 68,69 Merge overlapping areas and regulatory frameworks (merge) unify overlapping tools in the same territory (e.g., within the same MPA or coherent sector) 45 Promote collaboration between groups of stakeholders (collaboration) encourage actors to work toward the implementation of common objectives 45,55,65 Promote participatory research (participatory research) include non-scientists in MPA research processes (e.g., encourage collaboration between researchers and users in data collection) 45,70,71 Standardize management and monitoring indicators (standardization) use scientifically robust and standardized protocols and standardize monitoring systems 45 For each barrier and lever, a succinct definition is presented, as well as references from which they are derived. Barriers are grouped in three categories according to the component of the social-ecological system to which they refer (governance, resources, and intent; see experimental procedures).…”
Section: Intent Barriersmentioning
confidence: 99%
“…strengthen the continuous training between the different professions of the sea 45,52,55 Encourage stakeholder consultation (consultation) consult with stakeholders to determine the socioeconomic effects of strong protection, for the establishment of strategies, objectives, and regulations 45,55,65 Further communicate about the role of MPAs (communication) develop a clear, long-term communication strategy to promote the results of the researchers' work and raise awareness of the benefits of MPAs 45,49,[65][66][67] Increase and sustain the MPA budget (budget) increase and sustain the MPA budget 68,69 Merge overlapping areas and regulatory frameworks (merge) unify overlapping tools in the same territory (e.g., within the same MPA or coherent sector) 45 Promote collaboration between groups of stakeholders (collaboration) encourage actors to work toward the implementation of common objectives 45,55,65 Promote participatory research (participatory research) include non-scientists in MPA research processes (e.g., encourage collaboration between researchers and users in data collection) 45,70,71 Standardize management and monitoring indicators (standardization) use scientifically robust and standardized protocols and standardize monitoring systems 45 For each barrier and lever, a succinct definition is presented, as well as references from which they are derived. Barriers are grouped in three categories according to the component of the social-ecological system to which they refer (governance, resources, and intent; see experimental procedures).…”
Section: Intent Barriersmentioning
confidence: 99%
“…In Tautira, the rāhui implementation involved important relationships and interactions between local communities and scientists, which ultimately took root as arrangements defining the boundaries and design, objectives, expectations, and conditions of the protected areas to improve fishermen incomes. In the literature, such interactions are the foundation for tailoring coral reef management to local contexts in a way that acknowledges the importance of people's values (Kochalski et al 2019, Thiault et al 2020, local peer-topeer social networks (Christie et al 2009), cultural ecosystems services (Chiesura and De Groot, 2003;Hicks et al, 2013;Satz et al, 2013), customary management (Cinner and Aswani 2007, McMillen et al 2014, Delevaux et al 2018, and local forms of territoriality (Roué 2012, Bambridge 2013Donaldson 2019). As Aswani et al (2015 demonstrated, ILK learning can inform and guide the requisite decision-making process and offer a practical way for management efforts to become more efficient.…”
Section: How Do Iplc Stakeholders Feel About Indigenous Conservation Approaches As Related To Approaches Grounded In Conservation and Susmentioning
confidence: 99%
“…Coral bleaching events are increasing in severity, duration, and frequency globally with recovery windows shortening between heating events; for example, Australia's Great Barrier Reef in 2016, 2017, and 2020 (Hughes et al, 2019 ; Thiault et al, 2020 ), Kāneʻohe Bay, O‘ahu, Hawai‘i in 2014, 2015, and 2019 (Matsuda et al, 2020 ; Ritson‐Williams & Gates, 2020 ), Mo'orea, French Polynesia in 2002 (Penin et al, 2007 ) and 2019 (Burgess et al, 2021 ), and the Florida Keys in 2014 and 2015 (Fisch et al, 2019 ). In order to replenish reefs following mortality events, the recovery and persistence of reefs depend on reproduction, recruitment, and survival of new coral offspring (Doropoulos et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%